BALANCING REGIONAL LABOR MARKETS: CONCEPTUAL FOUNDATIONS AND SIGNIFICANCE IN THE SYSTEM OF REGIONAL DEVELOPMENT - PYKUS, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article presents a systematic analysis of imbalances in regional labor markets, which result from the mismatch between employers’ needs and the capabilities of the educational system, particularly in the training of skilled blue-collar workers. The purpose of the article is to substantiate the conceptual basis for balancing regional labor markets and to reveal their role within the system of regional development, considering contemporary challenges of socio-economic transformation, spatial disproportions, and the need to integrate regional employment policy into the strategic planning of sustainable territorial development. It is determined that these disparities have a multifaceted nature and manifest through spatial disintegration of labor resources, degradation of educational infrastructure, low level of integration between vocational education institutions and the business sector, as well as moral and technical obsolescence of material-technical bases and curricula. Special attention is paid to the challenges associated with the urgent need to adapt vocational education for retraining internally displaced persons and integrating vulnerable population groups, which is crucial for ensuring social stability in the regions. Six main types of imbalances are identified: educational-qualification, quantitative-structural, professional-sectoral, territorial-educational, educational mobility, and learning-information imbalances, which objectively hinder the effective functioning of the labor market. Modern theoretical approaches to balancing are analyzed, including spatial-economic models, human capital concepts, and socio-institutional theories that allow for considering the complexity and multidisciplinary nature of the issue. It is substantiated that ensuring the balance of regional labor markets is critically important for strengthening national security, stimulating economic recovery, curbing migration losses, and integrating Ukraine into the European economic space. The article proposes a set of measures aimed at enhancing interregional and intersectoral cooperation, developing inclusive employment forms, and implementing European standards in employment practices, which together will improve the competitiveness of regional labor markets and stabilize the socio-economic development of territories.
Keywords: labor market; vocational education; regional policy; imbalances; migration; recovery; European integration; human capital